2017
DOI: 10.1007/s00261-016-1036-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectral detector CT-derived virtual non-contrast images: comparison of attenuation values with unenhanced CT

Abstract: VNC images derived from novel dual layer spectral detector CT demonstrate attenuation values similar to unenhanced images in all tissues evaluated except for subcutaneous fat. Further study is needed to determine if attenuation thresholds currently used clinically for common pathology should be adjusted, particularly for lesions containing fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
79
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 15 publications
17
79
3
2
Order By: Relevance
“…Furthermore, their method to obtain this diagnostic equation combining ICs from both non‐enhanced and contrast‐enhanced CT images inevitably doubled the patients' radiation exposure. In this study, we used a recently implemented DECT scanner, which only a few studies used . This scanner achieves spectral separation using a different method from the previous fast‐kVp switching scanner in which the X‐ray tube rapidly modulates tube voltage .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, their method to obtain this diagnostic equation combining ICs from both non‐enhanced and contrast‐enhanced CT images inevitably doubled the patients' radiation exposure. In this study, we used a recently implemented DECT scanner, which only a few studies used . This scanner achieves spectral separation using a different method from the previous fast‐kVp switching scanner in which the X‐ray tube rapidly modulates tube voltage .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a recently implemented DECT scanner, which only a few studies used. [30][31][32][33][34][35] This scanner achieves spectral separation using a different method from the previous fast-kVp switching scanner in which the X-ray tube rapidly modulates tube voltage. 7,8,10 In contrast, our DECT scanner built with 2 scintillating layers has a single X-ray source that operates at a fixed tube potential, typically 120 or 140 kVp.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Fast kilovolt peak-switching (FS) scanners (HD-750 and Revolution CT; GE Healthcare, Waukesha, Wis) allow acquisition of dual-energy data by modulating the voltage of a single xray generator from low to high kilovolt peaks between alternating projections. (c) Dual-layered (DL) detector arrays have been implemented (IQon scanner; Philips, Best, the Netherlands) to create dual-energy projection data from a conventional 120 or 140 kVp scan (4,5). (d) A split-filter (SF) dual-energy mode has been implemented in a recent model (Edge CT, Siemens).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Durieux et al 2018 evaluated VNC images for abdominal depiction from a third generation dual-source dual-energy CT and pointed out that despite high accuracies of attenuation values for the liver and spleen with mean attenuation differences between 0-2 HU, there have been substantial differences in fluid, fat and renal tissue with mean differences as high as 32 HU. Other recent dual-energy studies also showed accurate iodine subtraction by VNC for depiction of the liver 23,24,35,36 . Further, overestimation of fat by VNC has also been reported for spectral-detector CT by Ananthakrishnan Our study showed differences between TNC and VNC of 1.8 ± 4.6 HU for CTA-Chest and −1.1 ± 5.9 HU in CTA-Abdomen in liver.…”
Section: Resultsmentioning
confidence: 82%
“…In this cohort we were able to show that VNC of TNC can reliably reduce increased liver density due to amiodarone deposition. As frequently applied in comparable studies, we used ROI-based measurements of mean attenuation [22][23][24][25]35 . Still, a volumetric assessment of attenuation covering an entire organ might be less susceptible for any measuring bias.…”
Section: Resultsmentioning
confidence: 99%